A CONSTRUÇÃO DO SENTIDO DO TRABALHO PARA A VIVÊNCIA DA INFÂNCIA NOS ASSENTAMENTOS - DORIGONI, DAIANE CRISTINE (2016)
This study addresses the relationship between the childhood´s development and the relationship between the works of settler families. The issue that drives this study is the relationship established in the community of the settled families, and establishes the meaning of work in the childhood. The substantiation was performed with an emphasis in the qualitative research, which is the representations of the acts and human expressions, seeking to interpret the meanings and intentions of social actors. The analysis data technique used was the Fairclough’s speech analysis, which aims to discuss theoretical and methodological language in the social practice. A survey was conducted with families that live in the settlements of Marcos Freire and Ireno Alves dos Santos, in the city of Rio Bonito do Iguaçu, Paraná, Brazil. From the collected data we can be observed that children have activities to be developed in the family’s environment, and that the performed mediations lead to an individual training for the job’s world. However, it was found that there isn’t an understanding by the researchers about the non-productive work yet, the one that generates meaning in the lives of individuals, but only an understanding that establishes the work as a way of life of surplus value and capital production. Because this work is need to be seen besides the capital’s system, that is, as a subjective constituent of each individual, while developed activity and not only as a reproduction mode without self-criticism. It was also evident that the childhood is seen as a form of preparation for the adult world, and not as a complete development, in which the execution of work activities is part of the routine and the emancipation of the involved ones in this process. Regarding the significance, they perform activities guided by the family organization, in which the meaning is individual and the meaning of the performed activities is understood collectively. This work refers to the understanding that the childhood still needs to be understood as a significant stage in the development of the individuals.